THE IMPACTS OF GRAMMATICAL COMPETENCE TOWARDS STUDENTS’ SPEAKING PROFICIENCY IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Sabarniati; Said Iskandar Zulkarnain (Getsempena English Education Journal, 2020)
This investigation is conducted standing on the gap that there are students of English who are good in speaking the target language but do not master the grammar well, and there are also found students who have adequate grammatical awareness but cannot express themselves orally. This study aims at identifying common grammatical errors occur while students are speaking and how students’ grammar ability influences their speaking performance. This study was conducted in a Basic Speaking Class of First Year English Department Students of UIN Ar-Raniry. The Students’ grammatical mastery was tested as well as examining their speaking proficiency in order to discover the impact that the grammar has over the speaking. Two teachers of speaking were also interviewed in order to verify a number of supportive information. The result of the study showed that “subject-verb agreement” (SVA) was the most frequent grammatical error occurred in students’ speaking practice. It was also admitted that grammatical issue has not a big deal in determining students’ ability to speak English.